Nutritional modulation of the gut microbiome in allogeneic hematopoietic stem cell transplantation recipients - Muratore, Edoardo; Leardini, Davide; Baccelli, Francesco; Venturelli, Francesco; Prete, Arcangelo; Masetti, Riccardo (Frontiers in Nutrition, 2022)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) represents a potentially curative strategy for many oncological and non-oncological diseases, but it is associated with marked morbidity and mortality. The disruption of gut microbiota (GM) eubiosis has been linked to major allo-HSCT complications, including infections and acute graft versus host disease (aGvHD), and correlates with mortality. This increasing knowledge on the role of the GM in the allo-HSCT procedure has led to fascinating ideas for modulating the intestinal ecosystem in order to improve clinical outcomes. Nutritional strategies, either by changing the route of nutritional supplementation or by administering specific molecules, are increasingly being considered as cost- and risk-effective methods of modulating the GM. Nutritional support has also emerged in the past several years as a key feature in supportive care for allo-HSCT recipients, and deterioration of nutritional status is associated with decreased overall survival and higher complication rates during treatment. Herein we provide a complete overview focused on nutritional modulation of the GM in allo-HSCT recipients. We address how pre transplant diet could affect GM composition and its ability to withstand the upsetting events occurring during transplantation. We also provide a complete overview on the influence of the route of nutritional administration on the intestinal ecosystem, with a particular focus on the comparison between enteral and parenteral nutrition. Moreover, as mounting evidence are showing how specific components of post transplant diet, such as lactose, could drastically shape the GM, we will also summarize the role of prebiotic supplementation in the modulation of the intestinal flora and in allo-HSCT outcomes.